Gender Differences in Listening Strategy Use: Correlation with Listening Proficiency - Nurhanipah, Gusti Safina; Karmina, Sari (Journal of Language Literature and Arts, 2024)
Studies have shown contradictory results regarding the influence of gender on listening strategies and the correlation between listening strategies and listening proficiency. Some research has found a correlation between students' listening strategies and their listening proficiency, while others have not. This study aims to investigate whether there are gender differences in the listening strategies employed by English Language Education (ELE) students and whether there is a correlation between these strategies and listening proficiency. A quantitative correlational design was used, involving 94 ELE students from the 2021 cohort at a public university in East Java. An online questionnaire with 24 items from the Listening Strategies Questionnaire (LSQ) was utilized to assess listening strategies, while scores from the UKBIng (English Language Proficiency Test) represented students' listening proficiency. The findings indicate no significant gender differences in the listening strategies employed, with a significance value greater than 0.05 and cognitive strategies being the most commonly used by both male and female students. However, a significant correlation was found between listening strategies and listening proficiency, with a correlation coefficient of 0.311. The study suggests enhancing the teaching and learning process by incorporating additional strategies beyond cognitive strategies to improve listening skills.